Pengelolaan limbah rumah kemas sayur melalui produksi pupuk organik cair - Undari, Desti; Arista, Nor Isnaeni Dwi; Natalia, Cristina Evi (Journal of Waste and Sustainable Consumption, 2024)
Background: The growth of the agricultural sector in Cipanas District, Cianjur Regency, West Java has increased the production of organic waste from vegetable packaging houses. This study aims to explore the method of converting vegetable waste into Liquid Organic Fertilizer (POC) for waste management and sustainable agriculture. Methods: This descriptive study evaluated the process of converting vegetable waste into POC in Cipanas District. The process includes soaking rice grits, mixing ingredients (rice soaking water, brown sugar solution, coconut water, vegetable waste), anaerobic fermentation for three weeks with periodic stirring, and harvesting. Findings: The study resulted in a description of the process of making POC from vegetable waste. POC has the potential to improve soil fertility holistically (physically, chemically, biologically) and has been proven effective in increasing the productivity of various types of vegetables. Conclusion: Utilization of vegetable waste as POC offers a sustainable solution for waste management and environmentally friendly agriculture. Although there are challenges in quality standardization and infrastructure, its economic potential and long-term benefits make this approach worthy of consideration in future agricultural strategies. Novelty: This study highlights the potential use of vegetable waste from packaging houses in Cipanas for POC production, integrating the concept of circular economy in agricultural waste management and the development of sustainable agricultural practices.